Clear Links Between Starting Methamphetamine and Increasing Sexual Risk Behavior: A Cohort Study Among Men Who Have Sex With Men. (15th April 2016) - Hoenigl, Martin; Chaillon, Antoine; Moore, David J.; Morris, Sheldon R.; Smith, Davey M.; Little, Susan J.
Abstract : Background: It remains unclear if methamphetamine is merely associated with high-risk behavior or if methamphetamine use causes high-risk behavior. Determining this would require a randomized controlled trial, which is clearly not ethical. A possible surrogate would be to investigate individuals before and after starting the use of methamphetamine. Methods: We performed a cohort study to analyze recent self-reported methamphetamine use and sexual risk behavior among 8905 men who have sex with men (MSM) receiving the "Early Test, " a community-based HIV screening program in San Diego, CA, between April 2008 and July 2014 (total 17, 272 testing encounters). Sexual risk behavior was evaluated using a previously published risk behavior score [San Diego Early Test (SDET) score] that predicts risk of HIV acquisition. Results: Methamphetamine use during the last 12 months (hereafter, recent-meth) was reported by 754/8905 unique MSM (8.5%). SDET scores were significantly higher in the 754 MSM with recent-meth use compared with the 5922 MSM who reported that they have never used methamphetamine ( P < 0.001). Eighty-two repeat testers initiated methamphetamine between testing encounter, with significantly higher SDET scores after starting methamphetamine [median 5 (interquartile range, 2–7) at recent-meth versus median 3 (interquartile range, 0–5) at never-meth; P < 0.001, respectively]. Conclusions: Given the ethical impossibility of conducting a randomized controlled trial, the results presented here provide the strongest evidence yet that initiation of methamphetamine use increases sexual risk behavior among HIV-uninfected MSM. Until more effective prevention or treatment interventions are available for methamphetamine users, HIV-uninfected MSM who use methamphetamine may represent ideal candidates for alternative effective prevention interventions (ie, preexposure prophylaxis).